Natural coagulates for wastewater treatment; a review for application and mechanism - Al-Sahari, Mohammed; Al-Gheethi, Adel; Radin Mohamed, Radin Maya Saphira (Springer Nature, 2020)
The increase of water demand and wastewater generation is among the global concerns in the world. The less effective management of water sources leads to serious consequences, the direct disposal of untreated wastewater is associated with the environmental pollution, elimination of aquatic life and the spread of deadly epidemics. The ﬂocculation process is one of the most important stages in water and wastewater treatment plants, wherein this phase the plankton, colloidal particles, and pollutants are precipitated and removed. Two major types of coagulants are used in the ﬂocculation process included the chemical and natural coagulants. Many studies have been performed to optimize the ﬂocculation process while most of these studies have conﬁrmed the hazardous effects of chemical coagulants utilization on the ecosystem. This chapter reviews a summary of the coagulation/ﬂocculation processes using natural coagulants as well as reviews one of the most effective natural methods of water and wastewater treatment.